Hemato-Serological Findings as Early signals in Nile Tilapia Oreochromis niloticus Treated with Benzalkonium Chloride (Baghdad Science Journal, 2023)
To evaluate the toxicity of benzalkonium chloride in aquaculture, the hemato-serological indices of Nile tilapia Oreochromis niloticus are used as biomarkers. Following exposure to three concentrations of benzalkonium chloride BAC 0.1, 0.25, 0.50, and 1 mg/l (BAC1,2,3 and 4) in aquaria for two durations 21 and 42 days, the microbiological assay in fish aquaria, in addition to blood parameters were assessed. Except for the mean difference between BAC2 and BAC3 (P > 0.05) at 42 days, the mean values of the bacterial counts revealed a significant difference between all compared groups (0.05 ≥ P ≤ 0.01). Following exposure to the lower concentrations of BAC (1, 2 and 3), the main blood parameters of Oreochromis niloticus namely red blood cells RBCs, and hemoglobin Hb decreased in fluctuated pattern when compared to control treatment (0.05 > P< 0.01), but interestingly peaked at the higher concentration (BAC4), despite there were no significant differences when compared to control (except hemoglobin at 42 days, P< 0.01). Contrarily, the white blood cells WBCs rapidly rose at the first concentration BAC1 (P< 0.01), particularly at the second duration, compared to the control treatments. The counted WBCs changed after exposure to the following two concentrations BAC2, BAC3, before peaking at the higher experimental concentration BAC4 (P< 0.01). The mean cells volume MCV, mean cells haemoglobin MCH and MCHC mean cells haemoglobin concentration exhibited a narrow fluctuation between control and BAC treated fish. Regarding biochemical findings, the average levels of cholesterol and triglycerides showed erratic behavior depending on BAC levels in treatment. The mean alanine transaminase ALT and aspartate aminotransferase AST levels fluctuated between the control and BAC1,2,3 before abruptly increasing at the higher BAC4, with significant differences (0.05 > P< 0.01) when control, BAC1,2,3, compared to BAC4, except AST between BAC3 and BAC4 (insignificant- 42 days). Following BAC exposure, other parameters, including protein and urea remained the same as in control fish. The alteration in some hemato-serological markers demonstrated how a compensatory mechanism is generated in response to the stress caused by exposure to biocides.